2016
DOI: 10.1039/c6ra02297a
|View full text |Cite
|
Sign up to set email alerts
|

First principles analysis of oxygen vacancy formation and migration in Sr2BMoO6 (B = Mg, Co, Ni)

Abstract: In this work, we present a detailed first-principles investigation on the stoichiometric and oxygen-deficient structures of double perovskites, Sr2BMoO6 (B = Mg, Co and Ni), using the density functional theory (DFT) method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…[15][16][17][18][19][20] Bivalent alkaline metals and transition metals (TM) were employed to substitute the Mo cations to generate double perovskites (e.g., Sr 2 MgMoO 6 , Sr 2 NiMoO 6 and Sr 2 CoMoO 6 ), which were used as the sulfur tolerant anode of IT-SOFCs. [21][22][23][24] Moreover, the trivalent Fe cation doped SrMoO 3 shows excellent catalytic capacity and oxygen ionic conductivity as a consequence of the mixedvalence of Mo 5+ /Mo 6+ and Fe 3+ /Fe 4+ , which were employed as both the anode and cathode for IT-SOFCs. [25][26][27][28] Likewise, the Crdoped SrMoO 3 is gradually attracting attention in the eld of IT-SOFCs anodes and rechargeable Li-air battery cathodes.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18][19][20] Bivalent alkaline metals and transition metals (TM) were employed to substitute the Mo cations to generate double perovskites (e.g., Sr 2 MgMoO 6 , Sr 2 NiMoO 6 and Sr 2 CoMoO 6 ), which were used as the sulfur tolerant anode of IT-SOFCs. [21][22][23][24] Moreover, the trivalent Fe cation doped SrMoO 3 shows excellent catalytic capacity and oxygen ionic conductivity as a consequence of the mixedvalence of Mo 5+ /Mo 6+ and Fe 3+ /Fe 4+ , which were employed as both the anode and cathode for IT-SOFCs. [25][26][27][28] Likewise, the Crdoped SrMoO 3 is gradually attracting attention in the eld of IT-SOFCs anodes and rechargeable Li-air battery cathodes.…”
Section: Introductionmentioning
confidence: 99%
“…[18,19] Furthermore, the catalytic activity of perovskite oxides is mainly influenced by B-site cations. [20,21] Peña-Martínez et al conducted an in-depth study on the influence of Bsite cations in oxides composed of La0.75Sr0.25Cr0.5X'0.5O3 (X '= Mn, Fe and Al) on electrode performance in SSOFCs. [22] Research has found that the performance of Mn doped anode oxides is higher than that of Fe and Al.…”
Section: Redox Stable Electrode 21 Single Phase Stable Electrodementioning
confidence: 99%
“…150,151 In addition, the absorption peak observed at 670 nm may have originated from the d–d electron transition of Fe 3+ or from the charge transfer transition between the interacting ions via the Fe 3+ + Fe 3+ → Fe 4+ + Fe 2+ reaction. 152–154 Based on the absorption spectrum, the indirect band gaps of the SFMO sample were determined to be 1.84 and 1.85 eV, respectively, which permit the absorption of visible light.…”
Section: Synthesis Of Hm Dp Oxidesmentioning
confidence: 99%